Sovietisation of Schools in 1940: ideological constraints from teachers, selebration of boshevik a coup d’état in in Schools of Šakiai County; (2) - Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2014)
This article contains archival factual material related to other primary schools in Šakiai County. It briefly assesses the situation of the teachers under the supervision of the so-called Šakiai County Committee and the local Bolsheviks (communists), Komsomol members and other collaborators, who had formed the structures of the county and district executive authorities. The superintendence manifested in the form of letters (often without even consulting the county inspection of elementary schools), various instructions (written or verbal) and the meetings organised for giving them, unexpected visits to the school during lessons, etc. In this article, the word ‘Bolsheviks’ is also used alongside the terms ‘Soviet(s)’ or ‘Communist(s)’, especially since the Republic of Lithuania was occupied by the Bolsheviks of the USSR in June 1940, and the Lithuanian Communists joined the All-Union Communist Party (Bolsheviks) or ACP(B) in 1940, where the ‘B’ in the parenthesis in the party’s name was intended to emphasize the Bolshevik character of the party that had taken over power in the former tsarist Russian Empire. The words ‘celebration’ and ‘celebratory’ and the constructions with these words are used in quotation marks because for the majority of society, for the parents of the pupils, and through them for the majority of the pupils, it was a celebration of the Bolshevik occupants and the local collaborators who served them. The article also uses the shorter construction of ‘October Revolution celebrations’ – ‘October celebrations’.